Pemilihan Tujuan untuk Melanjutkan Jenjang Pendidikan Siswa di SMAN 1 dan SMAN 2 di Kota Bagansiapiapi Kabupaten Rokan Hilir - Eli Nafa Maryanti; Achmad Hidir (Departement of Mathematics Education, 2023)
This study aims to determine the selection of goal for continiung education students at SMAN 1 and SMAN 2 in Bagansiapiapi City. Rokan Hilir Regency. This Study Uses an independent Variebel Consisting of actros,resources and noms, and the dependent variebel. SMAN 1 and SMAN 2 Bagan sapiapi. With respondents totaling 84 students. Data analysis techniques in this study used descriptive quantitative methods, correlation tests, and Simple Linear Regression tests. Correlation Test Results for resources sig. 0.723 <0.05, the alternative hypothesis (Ha) in this study is unacceptable. So it can be said that there is no relationship between resources and the selection of goals to continue their education students at SMAN 1 and SMAN 2 in Bagansiapiapi City, Rokan Hilir Regency, while the sig. 0.00 <0.05 then the alternative hypothesis (Ha) in this study is accepted. So it can be said that there is a relationship between norms and the selection of goals to continue their education students at SMAN 1 and SMAN 2 Bangko in Bagansiapiapi City, Rokan Hilir Regency. The results of the Simple Linear Regression Test obtained a coefficient of determination (R square) of 0.587, meaning that the influence of resources, norms on the selection of goals for continuing education students at SMAN 1 and SMAN 2 in Bagansiapiapi City, Rokan Hilir Regency is 58.7% while 41. 3% is influenced by other factors not examined in this study.